Kesesuaian Pediatric Nutritional Risk Score dengan Diagnosis Malnutrisi pada Anak di Rumah Sakit Umum Daerah Waled Kabupaten Cirebon - Firda Nafisa; Ali Manfaluthi Ahmad; Ineu Nopita (KOLONI, 2026)
Malnutrition in children remains a common health problem among hospitalized pediatric patients and may increase the risk of complications, length of stay, and mortality. Pediatric Nutritional Risk Score (PNRS) is one of the screening methods used to identify the risk of malnutrition in children at an early stage. This study aimed to determine the suitability of Pediatric Nutritional Risk Score with the diagnosis of malnutrition in children at Waled Regional General Hospital, Cirebon Regency. This study used an analytic observational design with a cross-sectional approach. The population consisted of all pediatric inpatients at Waled Regional General Hospital, Cirebon Regency. Samples were selected using consecutive sampling based on inclusion and exclusion criteria. The variables included Pediatric Nutritional Risk Score results and malnutrition diagnosis based on anthropometric parameters. Data were collected from medical records and observation sheets. Data analysis was performed using agreement tests by calculating sensitivity, specificity, and Kappa statistical tests. The results showed that Pediatric Nutritional Risk Score had a fairly good suitability with the diagnosis of malnutrition in pediatric patients. Most patients with high-risk PNRS scores were also diagnosed with malnutrition based on anthropometric assessment. Statistical analysis demonstrated a significant association between PNRS results and the diagnosis of malnutrition in children. Pediatric Nutritional Risk Score has a good level of suitability with the diagnosis of malnutrition in children and can be used as an initial screening method to detect the risk of malnutrition in hospitalized pediatric patients at Waled Regional General Hospital, Cirebon Regency.